Thermo/chemo-responsive shape memory effect in polymers : a sketch of working mechanisms, fundamentals and optimization - Huang, Wei Min (2013)
Based on the working mechanisms, a systematic literature review is logically presented to reveal that the thermo- and chemo- responsive shape memory effects (SMEs) are not the special phenomena of some particular polymers, but intrinsic features of most polymers (if not all). Subsequently, referring to the most recent experimental results and their theoretical origins, we reveal the fundamentals on the optimization of the SME in polymers and the approaches to design/synthesize polymeric materials with tailored features.